Exact solution of the harmonic problem for a rectangular plate in flat deformation by the method of initial functions - Olodo, Emmanuel; Adanhounme, Villévo; Hounkonnou, Mahouton Norbert (Zielona Góra: Uniwersytet Zielonogórski)
A wide range of applications is based nowadays on analytical developments which allow a precise and effective approach and short time of computations compared with the time required for numerical methods; in this way these developments are suitable for calculations in real time. This work proposes an approach for solving a two-dimensional harmonic problem of a rectangular plate under local surface loading using Vlasov`s symbolic method of initial functions and a general solution of the harmonic equation for a rectangle. Substituting the harmonic functions in symbolic form for the corresponding solutions allows us to give the exact solution of the problem in trigonometric form.
Keywords: harmonic functions; initial functions; flat deformation